EXHIBITION ABOUT ALBERT EINTEIN'S LIFE AND WORKS (1879-1955) - Souza Filho, Mohacir Pereira de [UNESP]; Osorio Araya, Ana Maria; Fiorato, Paulo Florato (Univ Matanzas, 2015)
This paper shows the results of a university extension project characterized as dissemination Scientific which through exposure of panels about Albert Einstein's life and works became aware the students about the importance of this scientist. The exhibition can be characterized as a non-formal education that occurs in a formal teaching space (inside the school environment). Members of the Teaching of Physics Group (NEF/UNESP) have searched Einstein's works and were made from six panels that addressed the Einstein's biography focus about your curiosities and hobbies. The theme is part of the school curriculum in the state of Sao Paulo. The survey was conducted with high school students of a public school in Lucelia/SP, Brazil. The methodology consisted in passing a documentary on the subject; then the students visited the panels and they responded the questions about the exhibitors. A questionnaire containing eight closed questions and one free question. Sixty six students completed the questionnaire and about analysis we can conclude the importance awaken students to the sciences initiating further research on this topic and others related to the Modern and Contemporary Physics.
Keywords: Dissemination scientific; physics teaching; history of science